PENETAPAN KADAR FENOLIK TOTAL EKSTRAK BATANG BAJAKAH TAMPALA (Spatholobus littoralis Hassk.) MENGGUNAKAN SPEKTROFOTOMETRI UV-VISIBLE - Noverda Ayuchecaria; Mochammad Maulidie Alfiannor Saputera; Rakhmadhan Niah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Bajakah tampala (Spatholobus littoralis Hassk) is one of the most widely grown plants in Central Kalimantan but has not been widely used. This plant has been empirically used to treat various diseases by the Dayak community. Efficacy obtained is suspected due to the presence of various phenol compounds in the plant. But until now there has been no further research to determine the levels of phenols contained therein. This study aims to determine the total phenolic levels in the stem of the Spatholobus littoralis Hassk. Phenolic compounds in the stem are extracted using maceration method with ethanol solvent. Total phenolic levels were determined using the UV-visible spectrophotometric method with Follin-Ciocalteau reagents and as a comparison used gallic acid. The results showed that in phytochemical screening, the stem extracts were contained phenolic compounds, tannins and saponins. Whereas in the quantitative examination it can be concluded that the average total phenolic content of the stem of the Bajakah extract with a concentration of 500 ppm is 12.33 mg GAE/g.